Participation of the Community of Kemadang Village, Tanjung Sari District in Tourism Activities in the South Coastal Area of Gunungkidul - Purnomo Saputro (CV. Ulil Albab Corp, 2024)
The Gunungkidul South Coastal area is one of the tourist destinations in Gunungkidul Regency. The existence of a tourist destination triggers the emergence of a chain of other activities related to tourism activities. This research aims to: (1) examine the level of participation of the Kemadang Village community in tourism activities in the Gunungkidul South Coastal Area, and (2) examine the impact of tourism activities in the area on the level of welfare of the Kemadang Village community. The research method used is a survey method. Data analysis includes (1) descriptive analysis, to examine community participation in tourism activities and examine the socio-economic and cultural conditions of the Kemadang Village community, (2)